FACTORS AFFECTING THE DECISION OF THE COMMUNITY OF TANJUNG PRIOK DISTRICT USING ONLINE TRANSPORTATION (GOJEK) - Iis Kartini; Featy Octaviany (ASIAN PUBLISHER, 2022)
This study aims to finds out what factors make the people of Tanjung Priok decide to use online transportation (Gojek). Gojek and Opang (Ojek Pangkalan) drivers are parties who have an obligation to take passengers to their destinations and get the right in the form of payments from passengers. Passengers are parties who have the right to be delivered to the place they want to go and have an obligation to provide wages to the driver. All data used in this study were obtained from interviews asked by researchers and answered by several sources, both from the driver and passenger side. Data analysis techniques used are interviews, observations and do some documentation, reduce data and present the data given in the form of a brief description of the results of interviews with several sources. The results showed that the price factor was the most influential factor in the Tanjung Priok community's decision to use online transportation (Gojek). Other factors such as the services provided by the driver also influence the Tanjung Priok community's decision to use online transportation (Gojek).